2010
DOI: 10.1111/j.1365-2648.2010.05433.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of accurate nursing documentation in patient records

Abstract: Aim. This paper is a report of a study conducted to describe the accuracy of nursing documentation in patient records in hospitals. Background. Accurate nursing documentation enables nurses to systematically review the nursing process and to evaluate the quality of care. Assessing nurses' reports in patient records can be helpful for improving the accuracy of nursing documentation. Method. In 2007-2008, we screened patient records (n = 341) from 35 wards in 10 hospitals in the Netherlands. The D-Catch instrume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
108
0
13

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(124 citation statements)
references
References 23 publications
3
108
0
13
Order By: Relevance
“…The evaluation of documentation comprehensiveness includes assessments of the relationships between the essential elements of the nursing process, including assessment, diagnosis, intervention and outcome [24]. Studies have shown a lack of accuracy and quality in nursing documentation in hospital settings [25,26] and a lack of accuracy in nursing documentation in nursing home settings [21,27].…”
Section: Introductionmentioning
confidence: 99%
“…The evaluation of documentation comprehensiveness includes assessments of the relationships between the essential elements of the nursing process, including assessment, diagnosis, intervention and outcome [24]. Studies have shown a lack of accuracy and quality in nursing documentation in hospital settings [25,26] and a lack of accuracy in nursing documentation in nursing home settings [21,27].…”
Section: Introductionmentioning
confidence: 99%
“…According to Jefferies et al [46], quality nursing documentation must meet seven criteria: (1) patient-centred, (2) contains the actual work of nursing, (3) reflects the nurses' clinical judgment, (4) is presented in a logical sequence, (5) is written in real time, (6) records variances in care and (7) fulfils legal requirements. However, even with this knowledge documentation remains poor [42], with insufficient documentation of; assessment and nursing care and inaccuracy of documentation evident [47]. This is compounded by incongruence between what is documented and the actual physical status of the patient [48] and limited documentation of the work of nurses [35].…”
Section: Discussionmentioning
confidence: 99%
“…Resultat og evaluering dokumenteres i større grad når det gjelder omfang og nøyaktig-het enn hva som er tilfellet for dokumentasjon av sykepleiediagnose og tiltak (6,8,16). Samtidig er det enighet om at sykepleieprosessen inneholder de teoretiske elementene for en fullstendig og nøyaktig sykepleiedokumentasjon (8,16).…”
Section: Introduksjonunclassified